Prevalence and Impact of Rheumatologic Pain in Cystic Fibrosis Adult Patients - Schmoll, Axelle; Launois, Claire; Perotin, Jeanne-Marie; Ravoninjatovo, Bruno; Griffon, Muriel; Carré, Sophie; Mulette, Pauline; Ancel, Julien; Hagenburg, Jean; Lebargy, François; Deslée, Gaëtan; Salmon, Jean-Hugues; et al. (Frontiers in Medicine, 2022)
Background With the improvement of cystic fibrosis (CF) patient survival, the prevalence of long-term complications increased, among them rheumatologic disorders. Methods The aim of this prospective study was to evaluate the prevalence of spinal and joint pain, and their impact on disability, anxiety, depression, and quality of life in CF adult patients. Results Forty-seven patients were analyzed, 72% of men, mean aged 28 years, with a mean body mass index of 22 kg/m2 and a mean FEV1% of 63%. Twenty-two patients (47%) described rheumatologic pain either spinal (n = 15, 32%) and/or joint pain (n = 14, 30%). Patients with spinal and/or joint pain were shorter (p = 0.023), more frequently colonized with Staphylococcus aureus (p < 0.008), had more frequent ΔF508 homozygous mutations (p = 0.014), and a trend for more impairment of the 6-min walking distance (p = 0.050). The presence of rheumatologic pain tended to be associated with disability according to the Health Assessment Questionnaire (HAQ) and anxiety. Compared with patients with no pain patients with both spinal and joint pain exhibited a more pronounced impact on the St George's Respiratory Questionnaire (SGRQ). Conclusion Rheumatologic pain is frequent in CF adult patients, and may affect daily living, anxiety and quality of life. Systematic assessment of rheumatologic pain should be included in the management of CF patients.